Nonlinear Dynamics of Internet Congestion Control: A Frequency-domain Approach - Gentile, Franco Sebastián (2014)
In this paper a fluid-flow model for TCP congestion avoidance combined with different AQM schemes is analyzed. The conditions for the appearance of Hopf bifurcations are stated analytically using frequency-domain techniques. The proposed methodology allows the characterization of the emerging periodic orbits, providing approximations of their amplitude and frequency. In addition, multiple oscillations and limit cycle bifurcations are found via numerical tools.